Qualidade microbiológica de alimentos servidos em restaurantes self-service - Chouman, Karina; Ponsano, Elisa Helena Giglio [UNESP]; Michelin, Aparecida de Fátima (My University, 2010)
Collective food services have been increasing worldwide, and the self-service restaurant has been the current preference by consumers. Considering the importance of hygienic quality of food, the microbiological composition of ready-to-eat food was assessed. In the second semester of 2008, 20 samples of meals, mainly meat-based foods, were collected from different self-service restaurants in Araçatuba city, SP. Bacteriological analyses were performed following the conventional methodologies, and the results were compared with the standards established by the effective Brazilian legislation. Coliforms at 35ºC were detected in 90% of analyzed samples. Coliforms at 45°C were found in 55% of the samples and, among these, in 63.63%, the occurrence of Escherichia coli was confirmed. Coagulase-positive staphylococci were detected in 10% of samples and no sample showed Salmonella spp. or Bacillus cereus contamination. Sulfite reducing clostridia at 42o C were not investigated in this study. These findings indicate the need for a rigorous approach for improving the sanitary conditions during preparation and presentation of ready-to-eat food, as the consumption of contaminated products represents a potential risk to public health.

Os serviços de alimentação coletiva têm se expandido em todo o mundo, sendo os restaurantes do tipo self-service a preferência atual dos consumidores. Considerando-se a importância da qualidade higiênica dos alimentos para a saúde da população, foi investigada a microbiota presente em alimentos prontos para o consumo. No segundo semestre de 2008, foram coletadas 20 amostras de refeições, à base de carne, prontas para o consumo, em diferentes restaurantes self-service da cidade de Araçatuba/SP. As análises bacteriológicas realizadas seguiram as metodologias convencionais e os resultados foram comparados com os padrões regulamentados pela legislação brasileira vigente. Das amostras analisadas, 90% foram positivas para coliformes a 35ºC. Coliformes a 45°C foram detectados em 55% das amostras e, destes, em 63,63% foi confirmada a ocorrência de Escherichia coli. A presença de estafilococos coagulase-positiva foi verificada em 10% das amostras; Salmonella spp. e Bacillus cereus não foram detectados. Não foram pesquisados os clostrídios sulfito redutores a 42ºC. Este estudo aponta a necessidade de atenção rigorosa quanto às condições sanitárias de preparo e exposição dos alimentos prontos para consumo, uma vez que a ingestão de produtos contaminados constitui um potencial risco para a saúde pública.
Microbiological quality of food from self-service restaurants
Keywords: Ready-to-eat food; Coliforms; Coagulase-positive staphylococci; Salmonella spp.; Alimentos prontos para consumo; Coliformes; Estafilococos coagulase-positiva; Salmonella spp.